Health Care Expenditures Associated With Pollution: Exploratory Methods and Findings - Alexander S. Preker; Olusoji O. Adeyi; Marisa Gil Lapetra; Diane-Charlotte Simon; Eric Keuffel (Ubiquity Press, 2017)
Background The research done for this paper is part of the background analysis undertaken to support the work of the Global Commission on Pollution, Health and Development, an initiative of The Lancet, the Global Alliance on Health and Pollution, and the Icahn School of Medicine at Mount Sinai. The paper expands on areas where the current literature has gaps in knowledge related to the health care cost of pollution. Objectives. This study aims to generate an initial estimate of total tangible health care expenditure attributable to man-made pollution affecting air, soil and water. Methods We use two methodologies to establish an upper and lower bounds for pollution related health expenditure. Key data points in both models include (a) burden-of-disease (BoD) at the national level in different countries attributable to pollution; and (b) the total cost of health care at the national level in different countries using standard national health accounts expenditure data. Findings Depending on which determinist model we apply, annual expenditures range from US$630 billion (upper bound) to US$240 billion (lower bound) or approximately three to nine percent of global spending on health care in 2013 (the reference year for the analysis). Although only 14 percent of global total for pollution related health care spending is in lower- and middle-income countries (LMICs) in our primary (lower bound) model, the relative share of spending for pollution related illness is substantial, especially in very low-income countries. Cancer, chronic respiratory and cardio/cerebrovascular illnesses account for the largest health care spending items linked to pollution even in LMICs. Conclusions These conditions have historically received less attention by national governments, international public health organizations and development/financial agencies than infectious disease and maternal/child health sectors. Other studies posit that intangible costs associated with environmental pollution include lower productivity and reduced income - components which our models do not attempt to capture. The financial and health impacts are substantial even when we exclude intangible costs, yet it is likely that in many LMICs poor households simply forgo medical treatment and lose household income as a result of man-made environmental degradation. Recommendations When evaluating the value of public health or environmental programs which prevent or limit pollution-related illness, policy makers should consider the health benefits, the tangible cost offsets (estimated in our models) and the opportunity costs.